Electrochemical polymerization of polypyrrole on carbon cloth@ZIF67 using alizarin red S as redox dopant for flexible supercapacitors. (1st March 2022) - Wang, Quanlu; Wang, Yikun; Zhang, Tingting; Wang, Yanmin; Zhang, Qiang; Li, Tingxi; Han, Yongqin
Abstract: Metal-organic frameworks (MOFs) are promising candidates for supercapacitors due to their intrinsic porous structure. However, their low conductivity limits their supercapacitive performances. Herein, carbon cloth/ZIF67/polypyrrole composites (CZPAs) are prepared by first in-situ growing ZIF67 on carbon cloth and then electrochemical polymerizing pyrrole on carbon cloth/ZIF67 utilizing alizarin red S (ARS) as redox dopant. The synergistic effects of ZIF67 and ARS including porous structure, doping effect and inducing limited/ordered growth of polyprrole are contributed to the improved electrochemical performances. The resulted composite doped by 35 mM ARS (CZPA-35) achieves the highest areal capacitance of 1198 mF cm −2 among the CZPAs. The asymmetric supercapacitor assembled by CZPA-35 and carbon cloth/active carbon as flexible electrodes demonstrates high areal capacitance (288 mF cm −2 ), high energy density (57.6 μWh cm −2 ) and power density (300.96 μW cm −2 ). Moreover, the flexible supercapacitor provides excellent cycle stability after 5000 cycles (87.1% capacitance retention) and flexibility (85% capacitance retention after bending angle of 180 °). This strategy can be extended to fabricate other kinds of flexible MOF/PPy composites for the potential application of flexible wearable and portable electronic products. Graphical abstract: Image, graphical abstract